Investigating changes in salivary microbiota due to dental treatment: A metagenomic analysis study for forensic purposes - Gul, Feyza; Karadayi, Sukriye; Yurdabakan, Zuhal; Ozbek, Tuelin; Karadayi, Beytullah (ELSEVIER IRELAND LTD, 2022)
The advent of next generation sequencing techniques as well as the existing traditional culture methods has enabled metagenomic studies on the usability of microbiomes for the forensic identification of individuals to gain momentum. However, before the utilization of microbiomes as a potential technique for real for-ensic case resolutions, it is necessary to understand the stability of the microbiota compositions in an individual's biological samples and the factors responsible for their variations. In the present study, we compared the microbiota compositions present in the saliva of individuals with active dental caries before and after treatment from a forensic and clinical perspective using an approach based on the sequencing of all the variable regions (V1-V9) of the bacterial 16 S rRNA gene. For this purpose, 10 individuals were included in the study comprising of 8 individuals between the ages of 18-50 years with at least 3 deep dentin caries as patients and 2 healthy individuals without any dental or gingival diseases as controls. Saliva samples were collected from the patients at two timepoints, before and after treatment, as well as from the healthy individuals (before and after control) at an interval of 1 month. The collected 20 saliva samples were subjected to metagenomic analysis using the MinION device, which was developed by Oxford Nanopore Technologies (ONT Oxford, UK). Bioinformatic analyses were performed on the obtained data and the re-sults were evaluated using statistical comparison methods and alpha/beta diversity analyses within the scope of the study objective. On evaluation using the distance metrics, it was observed that the microbial compositions in the saliva of individuals with active caries remained relatively stable after treatment. However, the relative abundance levels of bacteria of 28 genera and species showed statistically significant differences before and after treatment (p < 0.05). As a result, although the composition of salivary mi-crobiome remained relatively stable after caries treatment, there were significant changes in many types of bacteria, especially at the species level, between the BT and AT samples. Our results provide a framework for further forensic and clinical investigations regarding the factors that affect human salivary microbiome diversity.(c) 2022 Elsevier B.V. All rights reserved.
Keywords: Metagenomics; Microbiota; Forensic identification; Saliva; Caries treatment; Stability; ORAL MICROFLORA; CARIES; INDIVIDUALS; DIVERSITY; CHILDREN; Legal Medicine